Work with video display terminals among office employees. III. Ophthalmologic factors. - Boos, S. R.; Calissendorff, B. M.; Knave, B. G.; Nyman, K. G.; Voss, Margaretha (Scandinavian Journal of Work, Environment & Health, 1985)
The present ophthalmologic study is the third part of a major epidemiologic health investigation on work with a video display terminal (VDT). An initial study showed that VDT operators replying to a questionnaire reported more eye discomfort than a reference group not employed in VDT work and that women reported more eye discomfort, musculoskeletal discomfort, headache, and skin disorders than men, irrespective of whether or not they were employed in VDT work. In the present study the ophthalmologic history of eye diseases and eye discomfort yielded a much lower percentage response for symptoms and discomfort than the questionnaire, and, just as with visual acuity and refraction, there was no difference between the exposed and reference groups or between the men and women. The exposed subjects were found to be overcorrected in terms of presbyopia addition in relation to work distance. As regards ocular examination findings, low frequency rates were noted for pathological lens opacities. Opacities of this kind were slightly more frequent among the VDT operators than among the referents, but the difference was not statistically significant. There were no other differences in the ocular findings of the exposed and reference groups.